Breestraat 95 te Leiden, een statig huis uit de vijftiende eeuw (Bulletin KNOB, 2009)
Contrary to what the eighteenth-century façade leads one to suspect, building- historical research has shown that the listed building Breestraat 95 is six centuries old. In this research the original shell with large cellar, two high floors and the authentic roof construction were documented. On the basis of wood samples the house proved to have been built between 1405 and 1411.What was special was that the original façade could be reconstructed on the basis of the building-historical research, a sixteenth-century print and bird’seye- view maps. It turns out that the house had a high screen façade. Due to the height of the house it is as if it had more floors, which was intended to impress. The presence of corner turrets reinforced this effect.The rare combination of building-historical data and old representations has led to a reliable reconstruction, so that we have now come to know more about this type of medieval architecture, which no longer exists in Leiden.